Occurrence of Calamus acanthospathus Griff. and C. Travencoricus Bedd. in Bandarban District of Bangladesh - Ara, Rowshon (Indian Forester, 2010)
Two species of Rattans viz. Calamus acanthospathus Griff, and C. travencoroicus Bedd. Collected from Bandarban are being reported as new records for the first time from Bangladesh. Descriptive accounts of habits (both vegetative and reproductive structures) of these two species are reported. Nomenclature, geographical distribution and general uses of each species are provided. These species have been conserved in the canetum of Bangladesh Forest Research Institute (BFRI) and Institute of Forestry and Environmental Sciences, Chittagong University (IFESCU).